Hubungan Tingkat Pendidikan dengan Angka Kejadian Kondiloma Akuminata - Eka Silvia; Tusy Triwahyuni; M. Syafei Hamzah; Rian Hazni (ARTERI : Jurnal Ilmu Kesehatan, 2021)
Condyloma acuminata or what is often referred to as or genital warts caused by certain types of human papilloma virus (HPV) especially types 6 and 11. The level of education is one of the social factors that play a role in supporting a person to receive knowledge and information about condyloma acuminata disease, where the higher the level of education of a person usually has a greater understanding of health problems and their prevention, as well as the lower the level of one's education causes the more limited knowledge about the dangers of unhealthy behavior, so that they are not motivated to set a healthy lifestyle The purpose of this research is to determine the correlation between education level and the incidence of condyloma acuminata in dermatovenerology polyclinic of regional general hospital DR. H. Abdul Moeloek Lampung Province 2020. type of this research is analytic observational, with a cross-sectional study design, and with secondary data collection of condyloma acuminata and education level. The education level classification is adjusted according to the Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System. The technical of collecting the sample is total sampling. Data was collected by looking at medical record data and analyzed using the Spearman test. Results Obtained from 102 people according to the sample obtained. In patients with condyloma acuminata, the highest education level was 49.3%. The results of the Sperman statistical test obtain p = 0.009 (p <0.05) with a value of r = 0.256. Conclusion The final results showed that there was a significant relationship between the level of education and condyloma acuminata, the higher the level of education is lower, the higher the incidence of condyloma acuminata